A dynamic material flow model for the European steel cycle - Leon Rostek; Meta Thurid Lotz; Sabine Wittig; Andrea Herbst; Antonia Loibl; Luis Tercero Espinoza (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2022)
Steel is of extraordinary importance for the European economy as well as society, but is responsible for enormous energy consumption and greenhouse gas emissions. Therefore, steel flows are an obvious subject for the European climate protection. The quantification of steel stocks and flows is useful to be included in discussions regarding Circular Economy, energy system transformation and resource efficiency. Therefore, we developed a retrospective and dynamic material flow model covering the entire European steel and iron cycle from 2002 to 2019. Based on data by Worldsteel and assumptions mainly adopted by Cullen et al. (2012), the value and production chain of steel and iron products is covered by the model. It appears that the European steel and iron use reached a saturation from 2007 on, where the stock of steel in anthropogenic use phase reached around 5,600 Mt. In 2019, around 140 Mt of steel left the use phase, of which circa 6 Mt dissipated or are abandoned in place. Out of the remaining scrap, 110 Mt were collected as secondary raw materials for recycling. Recycling of steel in Europe reached a peak of approx. 140 Mt in 2007, from where on recycling declined equally to overall steel production leading to an almost constant recycling input rate of 57 %. The decline of steel recycling did not significantly affect the collection of steel scrap, but led to an increase of iron and steel scrap export. In 2019, 110 Mt of steel and iron were recycled in Europe, 65 % via EAF, 25 % via BOF and the remaining via ironmaking. Post-consumer waste is by mass more important than new scraps from production and manufacturing as evident in an old scrap ratio of 73 %. Further research could examine the effect of steel scrap prices on their use, further trace these export flows or analyse the potentials of secondary steel production for industry decarbonisation.
Keywords: 330; Stahlindustrie; Materialfluss; Klimaschutz; Kreislaufwirtschaft; Europa